2019
DOI: 10.36366/frontiers.v31i2.455
|View full text |Cite
|
Sign up to set email alerts
|

Assets-Based Learning Abroad: First-Generation Latinx College Students Leveraging and Increasing Community Cultural Wealth in Costa Rica

Abstract: This qualitative study counters deficit narratives about first generation Latinx students by exploring multi ple forms of community cultural wealth (CCW; Yosso, 2005) that 25 students leveraged and increased during service activities and homestays in Costa Rica. Through longitudinal data and with CCW as a conceptual framework, three key themes emerged First, s tudents were able to leverage their linguistic and familial capital to connect quickly and meaningfully with locals. Additionally, students drew upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…For study abroad, identified barriers explain why students chose not to study abroad and include family resistance, fear to travel, inability to take time off of work or wfamily, lack of knowledge to successfully navigate institutional bureaucracies, and personal deficits in social capital (Simon & Ainsworth, 2012). The counterbarrier construct shows that the current generation of nontraditional students are not constrained by identified barriers (Wick et al, 2019) because they use a range of social and cultural capitals to participate in college activities (Robertson, 2019).…”
Section: Theoretical Constructmentioning
confidence: 99%
“…For study abroad, identified barriers explain why students chose not to study abroad and include family resistance, fear to travel, inability to take time off of work or wfamily, lack of knowledge to successfully navigate institutional bureaucracies, and personal deficits in social capital (Simon & Ainsworth, 2012). The counterbarrier construct shows that the current generation of nontraditional students are not constrained by identified barriers (Wick et al, 2019) because they use a range of social and cultural capitals to participate in college activities (Robertson, 2019).…”
Section: Theoretical Constructmentioning
confidence: 99%
“…(pp. 15-16) Wick et al (2019) also documented tensions at the intersection of felt belonging or diasporic solidarity and economic inequity.…”
Section: Colonial Structures Decolonizing Desires: Education Abroad mentioning
confidence: 99%
“…But it is a concept that grew from Critical Race Theory (CRT) as situated in the specific histories of the United States. The field of education abroad has seen some applications of CRT (Chang, 2017;Wick et al, 2019), but in large part the field has situated itself within a discourse around intercultural competence that suggests it is "the ability to communicate effectively and appropriately in intercultural situations based on one's intercultural knowledge, skills, and attitudes" (Deardorff, 2006, p. 249). More recently, Bennett defined intercultural learning as "the acquisition of generalizable (transferrable) intercultural competence; that is, competence that can be applied to dealing with cross-cultural contact in general, not just skills useful for dealing with a particular other culture" (2012, p. 91).…”
Section: Community Cultural Wealthmentioning
confidence: 99%
See 2 more Smart Citations